Pengaruh Pendapatan Asli Daerah Dan Belanja Modal Terhadap Kinerja Keuangan Pemerintah Daerah (Studi Kasus pada Badan Pendapatan Daerah Provinsi Sumatera Utara) - Hastuti, Noviana Sri; Nasution, Dito Aditia Darma (Jurnal Riset AKuntansi dan Bisnis, 2024)
Regional government financial performance is an important aspect in public financial management. The ability of local governments to manage financial resources efficiently and effectively will influence the success of development and public services in the area. Therefore, it is necessary to evaluate the factors that influence local government financial performance. This research aims to analyze the influence of Regional Original Income (PAD) and Capital Expenditures on the Financial Performance of the Regional Government of North Sumatra Province, where financial performance is measured by the efficiency ratio. This research uses secondary data from the North Sumatra Province Regional Revenue and Expenditure Budget Realization Report (APBD) for the 2019-2022 period. Data analysis was carried out using the multiple linear regression method. The research results show that PAD partially has a positive and significant effect on local government financial performance, while capital expenditure has a negative and significant effect on local government financial performance. The coefficient of determination (R²) value in this research is 0.437, which means that the Regional Original Income and Capital Expenditure variables are able to explain 43.7% of the variation in Regional Government Financial Performance, while the remaining 56.3% is explained by other variables outside the research model..